A Multivariable Controller for the Start-up Procedure of a Solar Membrane Distillation Facility. Issue 4 (2018) - Gil, Juan D.; Roca, Lidia; Berenguel, Manuel; Guzmán, José Luis
Abstract: This paper presents a multivariable TITO (two inputs two ouputs) controller aimed to improve the start-up procedure of a Solar Membrane Distillation (SMD) facility, located at Plataforma Solar de Almería (PSA). The control structure includes PID controllers and decouplers, as well as a reference governor based on a real time optimizer. The filtered Smith Predictor (SP) control structure has been used for controlling one of the output variables, whereas a cascade control scheme is employed to control the other one. The proposed approach has been tested in simulation on a nonlinear model of the SMD facility, showing promising results.